Efektivitas Kurikulum Merdeka Terhadap Hasil Belajar Siswa Mata Pelajaran IPS di SMP Negeri Satu Atap 1 Montong Gading - Solihah, Amraini Wahidatus; Fahrurrozi, Muh (Alpatih Harapan Semesta, 2024)
This study aims to; 1) determine the implementation of the independent curriculum on student learning outcomes in social studies subjects at SMP Negeri Satu Atap 1 Montong Gading, 2) determine the effectiveness of the independent curriculum on student learning outcomes in social studies subjects at SMP Negeri Satu Atap 1 Montong Gading. This study is a type of quantitative correlational research. The population of this study was all students of SMP Negeri Satu Atap 1 Montong Gading. The number of research samples was 50 people. The data analysis technique used in this study was simple regression analysis. The results of this study indicate; 1) The implementation of the independent curriculum on student learning outcomes in social studies subjects at SMP Negeri Satu Atap 1 Montong Gading has been running but is still not optimal because the independent curriculum has only been running for one year and only class VII uses the independent curriculum. 2) The effectiveness of the Independent curriculum on student learning outcomes in social studies subjects at SMP Negeri Satu Atap 1 Montong Gading based on the results of the T test, that the independent variable of the independent curriculum (X) has a significant effect on the dependent variable of learning outcomes (Y). This is proven by testing from the two sides, the results obtained for the T table are 2.012. while for the T count on the independence variable is 2.309. Based on these results, the T count on the independent climate variable is greater than the T table (2.309> 2.012) and based on the level of significance (0.038 <0.05) it can be seen that Ho is rejected and Ha is accepted. So it can be concluded that the Merdeka curriculum has an effect on learning outcomes and the Merdeka curriculum is said to be effective on learning outcomes in social studies subjects at SMP Negeri Satu Atap 1 Montong Gading